Severe ARDS due to disseminated toxoplasmosis in a person with HIV successfully treated with ECMO: a case report - Medina, Daniel; Ávila, Renzo; Rodríguez-Sevilla, Graciela; Gumucio, Víctor; Bonilla, María; Abelenda-Alonso, Gabriela; Niubó, Jordi; Saumoy, Maria; Tiraboschi, Juan; Fuset, María Paz; Imaz, Arkaitz (Frontiers in Medicine, 2025)
Disseminated toxoplasmosis (DT) is an uncommon but severe complication associated with acquired immunodeficiency syndrome (AIDS). This case report describes the successful treatment of a 28-year-old male individual with AIDS who developed severe and life-threatening acute respiratory distress syndrome (ARDS) resulting from DT, in which extracorporeal membrane oxygenation (ECMO) was employed effectively.